Preparation of Au/ZnO/Fe3O4 Composite for Degradation of Tartrazine under Visible Light - Linh Vo Quang; Anh-Tuan Vu (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
Zinc oxide has been shown to be a potential photocatalyst under UV light but its catalytic activity is limited under visible light due to its wide bandgap energy and rapid recombination of electrons and holes. Besides the catalytic recovery is a challenging issue because of its dispersion in solution. Previous work has shown that the interaction of gold nanoparticles with ZnO can reduce the band gap energy (Eg) and plasmon resonance (SPR) as well as the formation of the Schottky barrier in Au/ZnO composite can reduce the recombination of electrons and holes. In this study, Au/ZnO/Fe3O4 (AZF) composites were prepared by a simple mixing method using polyvinyl alcohol (PVA) as a binder. As-prepared composites were characterized by Scanning Electron Microscope (SEM), Energy Dispersive X-ray Spectroscopy (EDS), X-ray Diffraction (XRD), UV-Vis Diffuse Reflectance (UV-Vis-DR), and Fourier Transform Infra Red (FT-IR). The catalytic efficiency of as-prepared samples was evaluated through the decomposition of tartrazine (TA), a colorant that is difficult to decompose in wastewater and has harmful effects on human health. The effects of reaction parameters such as the content of PVA, solution pH, and oxidizing agents (O2 and H2O2) on the catalytic efficiency were studied. The AZF at PVA of 0.0125 g showed the highest performance among as-prepared samples. With the presence of 12 mM H2O2 in the catalyst system, the degradation efficiency and reaction rate of TA in composite increased to 81.5% and 0.020 min−1, respectively. At this condition, photocatalysis and Fenton system catalysis occurred together. The catalytic mechanism of Tartrazine (TA) on composite was proposed and the reaction of TA was studied by the first-order kinetic model. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).